Study history to discover the chinese of the family - Casalino Sen, Carlota (2020)
This essay is a memory exercise around two aspects. The first is related to the remembrance of the great - grandfather who arrived in from China to southern Peru. The second, about my experience with the chinese - peruvian culture during my childhood and adolescence. During this exercise, I highlight a personal imprint from the everyday, so it is usually imperceptible and subjective.